(untitled) (Research, Society and Development, 2022)
The aim of this study was to analyze the spatial pattern of the distribution of dental caries in schoolchildren according to the high risk to this disease and to verify the presence of spatial dependence and its correlation with socioeconomic and geographic factors. The descriptive analysis was performed from the distribution of data in thematic maps and to identify spatial dependence, the Moran Global and Local indexes were used. The multivariate linear regression technique was performed with the oral health care model, distance to the nearest Health Unit and possession of social benefit, to verify which of the independent variables best describe the occurrence of the disease. The high risk of dental caries did not show spatial autocorrelation. However, it can be seen that large concentrations were randomly distributed throughout the municipality. In the regression analysis, a statistically significant difference was observed, conditioned by the distance in meters from the central point of the census sector to the nearest Health Unit (p = 0,003). It was not possible to establish a spatial autocorrelation of the high risk of dental caries. However, the presence of a statistically significant difference related to distance, demonstrates the importance of a good allocation of the health care point, to improve access and offer equitable assistance to citizens.